Improving the high temperature mechanical properties of alkali activated cement (AAC) mortars using recycled glass as aggregates. (September 2020) - Zhang, Binyu; He, Pingping; Poon, Chi Sun
Abstract: Waste glass recycling helps mitigating the problem of shortage of landfilling space, and it is especially of great importance for cities like Hong Kong where a local glass manufacturing industry is not available. This paper presents an innovative way of using recycled glass cullet (GC) in Alkali-activated cement (AAC) based mortars. Both mono-sized and mix-sized recycled GC were used as aggregates. The results showed that significant strength improvement was achieved after 2 h of exposure to 800 °C, despite of the size of the aggregates that was used. Up to 200% strength increment can be achieved for GC-AAC mortars with selected aggregate size. Meanwhile, Ordinary Portland Cement (OPC) based specimens were prepared for comparison and detrimental strength loss was observed. Microstructural analysis indicated that the improved mechanical properties after the high temperature test was attributed to the denser paste formed as a result of recycled glass aggregates annealing as well as the better bonding between the paste and the aggregates. Microhardness test showed that the heated AAC paste had significantly higher stiffness than the original paste before the elevated temperature exposure.